(untitled) (Bangladesh Journal of Anatomy, 2024)
Context: This study was carried out to observe the distance of paracentral lobule in relation to different points of cerebral hemisphere between adult male and female Bangladeshi population. Materials & Methods: This cross sectional study was conducted in the Department of Anatomy, Dhaka Medical College, Dhaka, during the period of January 2017 to December 2017. A total of 70 adult Bangladeshi male & female were selected, age ranging from 20-65 years. CT scan image of brain in midsagittal view was used for this study. Distance of paracentral lobule in relation to different points of cerebral hemisphere was measured and compared between adult male and female Bangladeshi population. Calculation was done using unpaired student’s ‘t’ test. Results: In male, mean distance from inferior most point of paracentral lobule to corpus callosum were 11.37±1.79 mm and 11.09±1.87 mm on right and left cerebral hemisphere respectively. In female, mean distance were 11.67±2.36 and 11.20±2.38 mm on right and left respectively. In male, distance from frontal pole to anterior most point of paracentral lobule of right and left were 89.21±5.22 mm and 88.82±5.28 mm respectively. In female, on right and left cerebral hemisphere, distance were 87.81±3.57 mm and 87.23±3.60 mm respectively. In male, distance from occipital pole to posterior most point of paracentral lobule of right and left cerebral hemisphere were 73.11±3.38 mm and 72.68±3.24 mm respectively. In female on right and left, distance were 71.86±4.67 mm and 71.49±5.08 mm respectively. Conclusion: There was no statistically significant difference regarding distance of paracentral lobule from different landmarks of cerebral hemisphere between adult male and female of Bangladesh. Bangladesh Journal of Anatomy July 2021, Vol. 19, No. 1, pp. 8-12